Factors Creating Employee Stress in Mergers and Acquisitions Practices in Bank and Financial Institutions of Nepal: Employee perspectives - Shrestha, Prakash; Chhetri, Guna Raj (Saptagandaki Journal, 2024)
This study aims to explore major factors creating employee stress in Merged and Acquisitions (M&As) practices in the context of Bank and Financial Institutions (BFIs) in Nepal. It has followed a qualitative approach to present the factors creating employee stress in mergers and acquisitions. Using a purposive sample approach, 60 employees from Nepalese BFIs— including clerical to executive-level personnel—were chosen and were asked to participate in a number of interviews and talks to learn more about the effects of M&A procedures. These employees were personally contacted at the corporate, branch, and head offices of five merged BFIs of Nepal. The findings identify twelve significant elements that contribute to employee stress as a result of merger and acquisition practices in BFIs. They include changes to compensation and benefits, change in leadership, fear and uncertainty, cultural shifts, job security, prioritizing self-protection, increased workloads and responsibilities, future, lack of trust and confidence, impact on career progression, approval delays, and communication gaps. Direct, observable changes (such as leadership and salary) are linked to the highest levels of stress, whereas more general, abstract worries (such as cultural changes and future related anxiety) are ranked lower. Proactively addressing these variables can reduce stress and increase the M&As practices' success. In fact, employee job stress can be reduced by encouraging employees to participate in productive work and maintaining strong motivation and commitment levels. Employee interaction, mentoring and peer support, employee well being, key staff retention, and cultural integration are the most crucial HR initiatives for effective M&As incorporation. All of these will assist in decreasing job stress among employees as a result of the M&As practices.